Sr1/2Ce5/14□1/7WO4: a new modulated ternary scheelite compound. Issue 3 (1st June 2017) - Damascena dos Passos, Rafael Hernandez; Arab, Madjid; Pereira de Souza, Carlson; Leroux, Christine
Abstract : A new ternary scheelite tungstate (Sr, Ce)WO4 phase was synthesized, with a two‐dimensional incommensurately modulated structure linked to partial ordering of Sr and Ce cations and vacancies as seen using high‐resolution electron microscopy. A band gap of 3.2 eV makes it a promising violet‐emitting compound. Abstract : For the first time, a ternary tetragonal scheelite structure tungstate with strontium and cerium cations, (Sr, Ce)WO4, was synthesized. As much as 35% Ce could be inserted into the structure, leaving of the (Sr, Ce) cation sites vacant. Partial ordering of Sr and Ce, with atomic displacements, were shown by high‐resolution electron microscopy. Two‐dimensional incommensurate modulations occur in this material, in small domains 20 nm in size. The band gap of this compound is significantly lower than the band gap of SrWO4 and this was related to the distortions of WO4 and (Sr, Ce)O8 polyhedra. The band gap value of 3.2 eV makes Sr1/2 Ce5/14 □1/7 WO4 a promising candidate for violet luminescence.